A Development of Personal Shopper Mobile Application - Azhari, Ameer Asfa; Mohd Yusof, Munirah (Applied Information Technology And Computer Science, 2023)
The movement control order (MCO) made in Malaysia on March of 2020 to fight against Covid19 has exponentially increase the growth of online shopping. Personal Shopper Mobile Application is a mobile application made with Flutter to fill in the gap between personal shopper and customer where there is currently no dedicated platform for users to purchase item efficiently. This project goes through an incremental prototyping methodology where the application is design, developed and test incrementally to solve the problem. The main significance of this project is that both customers and personal shopper can have a dedicated platform to view all available product at one medium rather than the various mediums used currently. Customers can also view all available product rather than going through the tedious step of asking personal shopper whether items are available. This project will help create a more effective, fluid and efficient process for all parties involved